1996
DOI: 10.1084/jem.184.6.2185
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Development in Culture from Thymic Precursor Cells in the Absence of Granulocyte/Macrophage Colony-stimulating Factor

Abstract: The earliest lymphoid precursor population in the adult mouse thymus had previously been shown to produce not only T cells, but also dendritic cell (DC) progeny on transfer to irradiated recipients. In this study, culture of these isolated thymic precursors with a mixture of cytokines induced them to proliferate and to differentiate to DC, but not to T lineage cells. At least 70% of the individual precursors had the capacity to form DC. The resultant DC were as effective as normal thymic DC in the functional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
1
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(145 citation statements)
references
References 38 publications
(70 reference statements)
12
129
1
3
Order By: Relevance
“…Although formal clonal proof of a common lymphoid/DC precursor is still missing, it is clear that these DC represent a distinct lineage with distinct cytokine requirements and transcription factor control (18,19). They also have a very much greater potential to produce IL-12 than either of the CD8 Ϫ DC populations (Ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although formal clonal proof of a common lymphoid/DC precursor is still missing, it is clear that these DC represent a distinct lineage with distinct cytokine requirements and transcription factor control (18,19). They also have a very much greater potential to produce IL-12 than either of the CD8 Ϫ DC populations (Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The murine lymphoid-related DC lineage differs from myeloidrelated DC both in the cytokine requirements for development and in transcription factor control (18,19). However, the expression of CD8␣ by the lymphoid-related DC does not appear to be essential for either their development or their function (18,20), so it may be a relic of their particular developmental history. No CD8 expression has been detected on human DC (21).…”
Section: Endritic Cells (Dc) 3 Collect Transport and Then Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, the CD134L ϩ cells were CD11c positive, suggesting that these cells are DC. They were also found to be CD11b ϩ and CD8␣ Ϫ , suggesting that they are of myeloid origin (49).…”
Section: Colitis Is Characterized By An Increase In the Number Of DC mentioning
confidence: 99%
“…As reviewed by Shortman et al in detail (16), the c-kit ϩ CD44 ϩ CD25 Ϫ (pro-T1) cells have previously been shown to have the capacity to form B cells, NK cells, and thymic DCs, as well as T cells, but not erythroid or myeloid cells, under the conditions tested at that time (15). The next downstream precursor, pro-T2 cells, appeared to have lost B cell and NK cell potential but still retained the capacity to form DCs.…”
Section: Figurementioning
confidence: 99%